Cotton : Market Setting, Trade Policies, and Issues - Baffes, John (World Bank, Washington, D.C., 2013)
The value of world cotton production in 2000-01 has been estimated at about $20 billion, down from $35 billion in 1996-97 when cotton prices were 50 percent higher. Although cotton's share in world merchandise trade is insignificant (about 0.12 percent), it is very important to a number of developing countries. Cotton accounts for approximately 40 percent of total merchandise export earnings in Benin and Burkina Faso, and 30 percent in Chad, Mali, and Uzbekistan. Its contribution to GDP in these and other developing countries is substantial, ranging between 5 and 10 percent. Cotton supports the livelihoods of millions in developing countries (at least 10 million in West and Central Africa) where it is a typical, and often dominant, smallholder cash crop. The cotton market also has been subject to considerable market intervention-subsidization in the European Union and the United States, and taxation in Africa and Central Asia. During the past three seasons, annual direct support averaged $4.5 billion. The author reviews the market setting and policy issues and gives recommendations on how industrial and developing cotton-producing countries can improve the policy environment.